A new method to statistically describe microcatheter tip position in patient-specific aneurysm models. (16th October 2018) - Nawka, Marie Teresa; Buhk, Jan-Hendrik; Gellissen, Susanne; Sedlacik, Jan; Fiehler, Jens; Frölich, Andreas Maximilian
Abstract : Background and purpose: Evidence on how to select microcatheters to facilitate aneurysm catheterization during coil embolization is sparse. We developed a new method to define microcatheter tip location inside a patient-specific aneurysm model as a 3-dimensional probability map. We hypothesized that precision and accuracy of microcatheter tip positioning depend on catheter tip shape and aneurysmal geometry. Materials and methods: Under fluoroscopic guidance two to three operators introduced differently shaped microcatheters (straight, 45°, 90°) into eight aneurysm models targeting the anatomic center of the aneurysm. Each microcatheter position was recorded with flat-panel CT, and 3-dimensional probability maps of the microcatheter tip positions were generated. Maps were assessed with histogram analyses and compared between tip shapes, aneurysm locations and operators. Results: Among a total of 530 microcatheter insertions, the precision (mean distance between catheter positions) and accuracy (mean distance to target position) were significantly higher for the 45° tip (1.10±0.64 mm, 3.81±1.41 mm, respectively) than for the 90° tip (1.27±0.57 mm, p=0.010; 4.21±1.60 mm p=0.014, respectively). Accuracy was significantly higher in posterior communicating artery aneurysms (3.38±1.20 mm) than in aneurysms of the internal carotid artery (4.56±1.54 mm, p<0.001). Conclusion: Our method can be used tostatistically describe statistically microcatheter behavior in patient-specific anatomy, which may improve the available evidence guiding microcatheter shape selection. Experience increases the ability to reach the intended position with a microcatheter (accuracy) that is also dependent on the aneurysm location, whereas catheter tip choice determines the variability of catheter tip placements versus each other (precision). Clinical validation is required.